Research of Probability Symmetric Allocation Storage in Distributed Storage System - Shengrong Lu; Hanming Li (Institute of Advanced Engineering and Science, 2014)
The goal of optimal allocation is to increase the stored data availability subject to minimize the storage budget. The symmetric allocation based on the network coding is proved to be optimal without considering the nodes availability in distributed storage system. Because of network conditions and node inherent property, each node has different availability. This paper focuses on the optimization distributed data storage problem with nodes availability. Based on probability model of storage system, we re-define the symmetric allocation as the probability symmetric allocation, and proposed probability symmetric allocation model and strategy which are proved to be optimal in the general condition based on SVM. Comparing to the symmetric allocation proposed by Leong D. et al., The proposed probability symmetric allocation scheme improves the data availability, and is more practical method for distributed storage system. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5100